2023
DOI: 10.1002/ep.14203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of piston bowl geometry and spray angle on engine performance and emissions in HCCI engine using multi‐stage injection strategy

Abstract: The homogeneous charge compression ignition (HCCI) and combustion chamber geometry play significant roles in improving the potential of compression ignition engines and their environmental sustainability. However, a major hindrance to the progress of HCCI technology has been the notable decline in brake thermal efficiency and emit high levels of hydrocarbon (HC) and carbon monoxide (CO) which is mainly due to the low temperatures during combustion and low post oxidation of these components. Combustion chambers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(86 reference statements)
0
0
0
Order By: Relevance
“…They also indicated that pressure inside the cylinder increased and soot emission decreased with increasing injection pressure and the highest in-cylinder pressure was obtained at approximately 11.0 MPa with the use of 150° spray angle and 1000 bar injection pressure in dual swirl piston bowl geometry. Mishra et al (2023) investigated the influence of hemispherical and toroidal piston bowl geometries on engine performance in a CI engine with HCCI combustion mode. In addition, they used variable spray angles to provide a good mixture of air and fuel in the piston bowl and to reduce fuel density in certain areas of the combustion chamber.…”
Section: Introductionmentioning
confidence: 99%
“…They also indicated that pressure inside the cylinder increased and soot emission decreased with increasing injection pressure and the highest in-cylinder pressure was obtained at approximately 11.0 MPa with the use of 150° spray angle and 1000 bar injection pressure in dual swirl piston bowl geometry. Mishra et al (2023) investigated the influence of hemispherical and toroidal piston bowl geometries on engine performance in a CI engine with HCCI combustion mode. In addition, they used variable spray angles to provide a good mixture of air and fuel in the piston bowl and to reduce fuel density in certain areas of the combustion chamber.…”
Section: Introductionmentioning
confidence: 99%